Design and construct a perpetual motion device - Chan, Ren Wei. (2011)
In the last century, people all over the world have numerous failed attempts to design and construct a functional perpetual motion device. The attractiveness of such device is due to its ability to benefit the world by providing cheap and clean energy for a more sustainable environment.